Casablanca colonial myths and architectural ventures - Cohen, Jean-Louis 1949-2023 (Monacelli Press, 2002)
Casablanca is a city of international renown, not least because of its urban structures and features. Celebrated by colonial writers, filmed by Hollywood, magnet for Europeans and Moroccans, Casablanca is above all an exceptional collection of urban spaces, houses, and gardens. While it is true that Casablanca developed as a port city well before the introduction of the French in 1907, it unquestionably ranks among the most significant urban creations of the twentieth century, attracting remarkable teams of architects and planners. Their commissions came from clients who were interested in innovation and modernization, thereby fostering the emergence of Casablanca as a laboratory for legislative, technological, and visual experimentation. Having studied the city for ten years, Jean-Louis Cohen and Monique Eleb trace, from the late nineteenth century to the early 1960s, the rebirth of a once-forgotten port and its metamorphosis into a teeming metropolis that is an amalgam of Mediterranean culture from Tunisia, Algeria, Spain, and Italy. The extensive presentation of the significant buildings of this hybrid city -- where, alongside the French, Muslim and Jewish Moroccan patrons commissioned provocative buildings -- is drawn from French and Moroccan archives, including hundreds of previously unpublished photographs. Cohen and Eleb focus as much on Casablanca's diverse social fabric as its urban spaces, chronicling the clients, inhabitants, and inventive architects who comprise the human component of an essential yet overlooked episode of modernism.
Keywords: Geschichte 1900-2000; Geschichte 1900-1960; Architecture - Maroc - Casablanca - 20e siècle; Urbanisme - Maroc - Casablanca - Histoire - 20e siècle; Architektur; Geschichte; Stadtplanung; Architecture -- Morocco -- Casablanca -- History -- 20th century; City planning -- Morocco -- Casablanca -- History -- 20th century; Städtebau; Casablanca (Maroc) - Constructions; Casablanca (Morocco) -- Buildings, structures, etc; Casablanca; Bildband